Ferroelectric and dielectric properties of cement pozzolan –PSrZT ceramic composites with PVDF polymer as a third phase - N. Jaitanong (2018)
© 2018 Taylor & Francis Group, LLC. Fabrication and electrical properties of Ordinary Portland cement (OPC), fly ash (FA) and lead strontium zirconate titanate (PSrZT) ceramic composites were investigated. Ordinary Portland cement was partially replaced with fly ash at 10% by weight of binder. PSrZT ceramic of mid particle sizes (450 µm) were used at 50% by volume to produce the 0–3 connectivity composites. A third phase addition which PVDF were used 3–7% by volume. The composites were mixed and pressed together and cured with 97% RH in water bath chamber for 3 days before measurements. The dielectric properties were measured under room temperature. The ferroelectric properties and microstructure of composites were then also investigated. The results show these composites have a limited amount of PVDF of about 5.0 volume% was optimum for enhancing the dielectric and ferroelectric properties.